Unbridled Calling : A Biography of Alberto Gerchunoff - Szurmuk, Mónica, (Jewish Latin America ;, 2024)
How can a child born in the Russian Pale at the end of the 19th century become one of the most celebrated journalists in Latin America and a writer admired by Jorge Luis Borges? In this biography, Mónica Szurmuk, delves into the different aspects of the life of writer, journalist, and politician Alberto Gerchuinoff. Thoroughly researched in four different continents, this book is as much an account of the life of Alberto Gerchunoff, as an investigation into the Jewish world of the first half of the twentieth century, and the different spaces where Jewish and Latin American cultural and political life intersect.